2008
DOI: 10.1590/s1516-89132008000600019
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of whey lactose by immobilized β-Galactosidase

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…These results demonstrate that the immobilization process was effective in maintaining the operational stability of the immobilized enzyme. Comparable results with b-galactosidase from A. oryzae immobilized in silica are reported by Mariotti et al [57] where the operational stability studies were carried out in packed bed reactor for a flow rate of 0.5 mL/min and the activity was reduced by 24 % after 130 days of operation. Klein et al [58] reported that b-galactosidase from K. lactis immobilized on chitosan [59].…”
Section: Reactor Operational Efficiencysupporting
confidence: 76%
“…These results demonstrate that the immobilization process was effective in maintaining the operational stability of the immobilized enzyme. Comparable results with b-galactosidase from A. oryzae immobilized in silica are reported by Mariotti et al [57] where the operational stability studies were carried out in packed bed reactor for a flow rate of 0.5 mL/min and the activity was reduced by 24 % after 130 days of operation. Klein et al [58] reported that b-galactosidase from K. lactis immobilized on chitosan [59].…”
Section: Reactor Operational Efficiencysupporting
confidence: 76%
“…The advantages of immobilized enzymes in respect to their free counterpart are well known. There are various methods for immobilization of enzyme ␤-galactosidase on different carriers -on the graphite surface with glutaraldehyde (GA) as cross-linking agent [2], on silica gel using GA [3], on Al 2 O 3 by physical adsorption [4] and est.…”
Section: Introductionmentioning
confidence: 99%
“…Also here, immobilization improved continuous lactose hydrolysis [7]. Accordingly, Mariotti et al [69] indicated that the stability and the hydrolysis activity of whey lactose by a silica-immobilized beta-galactosidase from A. oryzae within a continuous reactor process increased compared to non-immobilized systems. This study confirms the advanced performance of the immobilized enzyme at long-term processes.…”
Section: Advantages and Disadvantages Of Immobilized Enzymesmentioning
confidence: 70%
“…This study confirms the advanced performance of the immobilized enzyme at long-term processes. The halflife of the biocatalyst in a lactose solution at 40°C was estimated to be 12 months [69].…”
Section: Advantages and Disadvantages Of Immobilized Enzymesmentioning
confidence: 99%